Visual perceptual salience and novel referent selection in children with and without autism spectrum disorder. (March 2022) - Venker, Courtney E.; Neumann, Dominik; Aladé, Fashina
Background & Aims: Many young children with autism spectrum disorder (ASD) demonstrate striking delays in early vocabulary development. Experimental studies that teach the meanings of novel nonwords can determine the effects of linguistic and attentional factors. One factor that may affect novel referent selection in children with ASD is visual perceptual salience—how interesting (i.e., striking) stimuli are on the basis of their visual properties. The goal of the current study was to determine how the perceptual salience of objects affected novel referent selection in children with ASD and children who are typically developing (TD) of similar ages (mean age 3–4 years). Methods: Using a screen-based experimental paradigm, children were taught the names of four unfamiliar objects: two high-salience objects and two low-salience objects. Their comprehension of the novel words was assessed in low-difficulty and high-difficulty trials. Gaze location was determined from video by trained research assistants. Results: Contrary to initial predictions, findings indicated that high perceptual salience disrupted novel referent selection in the children with ASD but facilitated attention to the target object in age-matched TD peers. The children with ASD showed no significant evidence of successful novel referent selection in the high-difficulty trials. Exploratory reaction time analyses suggested that the children with autism showed "stickier" attention—had more difficulty disengaging (i.e., looking away)—from high-salience distracter images than low-salience distracter images, even though the two images were balanced in salience for any given test trial. Conclusions and Clinical Implications: These findings add to growing evidence that high perceptual salience has the potential to disrupt novel referent selection in children with ASD. These results underscore the complexity of novel referent selection and highlight the importance of taking the immediate testing context into account. In particular, it is important to acknowledge that screen-based assessments and screen-based learning activities used with children with ASD are not immune to the effects of lower level visual features, such as perceptual salience.